The Influence of Product Innovation and Innovation-Based Marketing on The Competitiveness of MSMEs and its Impact on Local Economic Growth in West Java - Rusdian, Suca; Tojiri, Yusuf; Yakin, Ipa Hafsiah (Universitas Mercu Buana, 2025)
Objective: Regional economic growth is greatly influenced by the ability of micro, small, and medium enterprises (MSMEs) to innovate and adapt to market changes. This study aims to analyze the effect of product innovation and innovation-based marketing on the competitiveness of MSMEs and their impact on local economic growth in West Java Province.Methodology: This research is an explanatory quantitative study using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach. The research population includes all MSME actors in the creative industry, agribusiness, and service sectors in West Java, with a sample of 200 respondents selected using purposive sampling. Data collection was conducted through a structured questionnaire that had been tested for validity and reliability.Findings: The results showed that product innovation and innovation-based marketing had a positive effect on the competitiveness of MSMEs, and competitiveness was proven to mediate the influence of these two variables on local economic growth. These findings suggest that enhancing innovation capacity and adopting adaptive marketing strategies are crucial factors in strengthening the market position of MSMEs while driving regional economic development.Conclusion: The practical implication of this study is the need for local government policy support to enhance the innovation ecosystem and digitization of MSMEs, creating inclusive and sustainable regional economic development